PENGARUH HARDENING PADA BAJA JIS G 4051 GRADE S45C TERHADAP SIFAT MEKANIS DAN STRUKTUR MIKRO - Sarjono, Koos (Badan Pengkajian dan Penerapan Teknologi, 2009)
Steel represents a metallic material which is still dominantly used in the engineering industry and mechanical construction. In order to fulfil the industrial demand, the high quality and mechanical properties of steel has to be always available.It is necessary to conduct a heat-treatment process to identify the improvement of mechanical properties and microstructure of steel JIS G 4051 grade S 45 C .Results of the heat-treatment process indicate that the maximum tensile strength of the investigated steel is 1074 MPa , it is earning from the warm-up temperature 860 °C and the highest hardness of the investigated steel is 579 HV it is earning from the warm-up temperature 920 °C . These results meet to AISI – SAE 1045 or JIS G 4051 grade S 45 C standard.